Особливості забезпечення безпеки осіб у досудовому кримінальному провадженні - Копетюк, М.; Kopetyuk, N. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено особливості забезпечення конституційних прав і свобод людини, зокрема забезпе- чення безпеки осіб у досудовому кримінальному провадженні. Проведено порівняльно-правовий аналіз КПК України 1960 та 2013 рр. щодо обов’язків посадових осіб із забезпечення безпеки учасників кримінального провадження. З’ясовано прогалини чинного КПК України, обґрунтовано та запропоновано пропозиції з удосконалення чинного законодавства в дослідженій сфері. The article investigates the peculiarities of the safety provisions in pretrial criminal proceedings. A comparative law research of the CPC of Ukraine in 1960 and 2013 is held in a part of the duties of officers to ensure the safety of participants of criminal proceedings The author considers that the special measures focused on the ensuring the safety of the persons involved in the criminal proceedings are the legal, organizational as well as technical and other measures to protect the life, health, housing, property, honor and dignity of the persons against illegal encroachments in order to create comfortable environment for the implementation and enforcement of justice. The gaps in the existing CPC of Ukraine are defined and the justified proposals to improve legislation in the investigated area are given. In particular, the author offers to add the third part to the Article 59 of the Constitution of Ukraine. It should be worded as following: “Everyone has the right to ensure his safety in the presence of a real threat to life, health or property”. The author notes that in the 2012 CPC of Ukraine the institute of ensuring the safety of the criminal proceedings participants is not specifically defined and specialized, as well as “sputtered” in various articles. It is supported the proposal to amendment the Code of Criminal Procedure for clarification of participants of criminal proceedings the right to safety when the separate process-verbal should be executed.
The Safety Provisions Peculiarities at the Pretrial Criminal Proceedings
Keywords: забезпечення безпеки; кримінальне провадження; досудове розслідування; safety provisions; criminal proceedings; pre-trial investigation